MEMBANGUN PENGUATAN PEMAHAMAN DAN KESADARAN WAKAF MASYARAKAT PESANTREN GONTOR MELALUI GISWAF - Syahruddin; Khurun'in Zahro'; Arizqiya Nurfattah; Azzam Al Hanif; Roudhoh Hannaris Said (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Waqf has a strategic role in the economic empowerment of Muslims through innovative and productive utilization. However, public understanding and literacy about waqf is still relatively low. This community service programmed aims to increase waqf awareness and literacy through the Indonesian Waqf Awareness Movement (GISWAF) activities implemented at Pondok Modern Darussalam Gontor (PMDG) Female Campus. The implementation method involves a participatory approach consisting of education, case study discussion, practical training, and pre-test and post-test evaluation. The programmed was designed to determine the extent of understanding and awareness of waqf after the counselling. The pre-test and post-test results of the 150 Gontor teacher participants showed that the Gontor teachers' understanding and awareness of productive waqf and some of its schemes were not very deep. It can be seen from the percentage of answers 54% correct and 46% incorrect, which is still dominated by incorrect answers. Meanwhile, the post-test has shown a significant difference, which is dominated by correct answers with a percentage of 87% correct and 13% incorrect answers. Thus, it is clear that the impact of the counselling has changed for now, but there needs to be development and sustainability so that the understanding gained by Gontor teachers can be maximized. Participants also demonstrated the ability to design and manage productive waqf projects in the education and economic sectors. However, challenges related to technical understanding and implementation remain, which require ongoing mentoring. Suggestions include the digitalization of training modules, strategic partnerships with waqf institutions, and the development of an online platform to expand the impact of the programmed. These efforts are expected to create waqf literacy agents that contribute to the welfare of the ummah.